Sulphur Containing Heterocyclic Compounds as Anticancer Agents - Kaur, Balwinder; Singh, Gurdeep; Sharma, Vikas; Singh, Iqubal (Anti-Cancer Agents in Medicinal Chemistry, 2023)
After cardiovascular disease, cancer is the most common cause of death worldwide. Due to their versatility, heterocyclic compounds play an important role in drug discovery. Medical remedies are constantly being discovered, especially for catastrophic disorders such as cancer. Here, this review is focused on sulphur containing heterocyclic compounds as anticancer agents. Sulphur is found in a variety of vitamin cofactors, sugars, and nucleic acids, and it also plays a function in controlling translation by sulphurating transfer RNA. Sulphur has obtained a lot of interest in the anticancer research medicinal fields. Thiophene derivatives were tested for anti-proliferative activity against breast cancer cells in a recent screening study, and the bulk of chemicals exhibited potent inhibitory effects. In recent years, azoles such as thiazole and thiadiazole structures have gained prominence in cancer research.
Keywords: heterocycles